Long-Term Efficacy of CRT, Lucid, Euclid, and IBright Orthokeratology Lenses in Controlling Myopia Progression in Children and Adolescents: A 36-Month Retrospective Cohort Study - Xi W; Li H; Qi W; Tan T; Wang L (Clinical Ophthalmology)
Wulan Xi,1 Huixia Li,2 Wenping Qi,3 Tingting Tan,1 Lin Wang4 1Department of Refractive Error Treatment, Tongliao Chaoju Eye Hospital, Tongliao, People’s Republic of China; 2Department of refractive error treatment, Inner Mongolian Chaoju Eye Hospital, Hohhot, People’s Republic of China; 3Department of Refractive Error Treatment, Baotou Chaoju Eye Hospital, Baotou, People’s Republic of China; 4Department of Ophthalmology, The Fourth People’s Hospital of Shenyang, Shenyang, People’s Republic of ChinaCorrespondence: Tingting Tan, Department of refractive error treatment, Tongliao Chaoju Eye Hospital, Tongliao, People’s Republic of China, Email tantingting@chaojueye.com Lin Wang, Department of Ophthalmology, The Fourth People’s Hospital of Shenyang, Shenyang, People’s Republic of China, Email wlin128@163.comPurpose: This study aimed to compare the efficacy and safety of four types of orthokeratology (OK) lenses (CRT, Lucid, Euclid, and IBright) in controlling mild to moderate myopia progression among children and adolescents over 36 months.Methods: This retrospective study analyzed clinical records of 219 children (438 eyes) who wore OK lenses for 36 months. Clinical data for the four commonly used OK lenses were collected and analyzed using one-way analysis of variance (ANOVA) and Pearson’s chi-squared test.Results: At baseline, no significant differences were observed among the four groups in terms of age, sex, spherical equivalent, corneal curvature, or corneal thickness (all P > 0.05). All OK lenses effectively controlled myopia progression over the observation period, with axial length changes not exceeding 1.0 mm. At the 36-month follow-up, the IBright group showed the largest flat keratometry (K1) curvature change at 3 months (− 2.40 ± 0.97 D), while other groups showed no significant differences at subsequent time points. In terms of steep keratometry (K2) curvature, the Lucid group exhibited the largest change at 24 months (− 3.07 ± 1.50 D), but no significant differences were observed among groups at other time points. Axial length changes showed no statistically significant differences among the four OK lenses across follow-up visits (P > 0.05). Subgroup analysis indicated greater axial elongation in children under 12 years old compared to those over 12 years. Among children with corneal thickness less than 530 μm, the CRT group demonstrated the largest K1 curvature change. The incidence of adverse events was comparable across groups (P > 0.05).Conclusion: All four OK lenses demonstrated comparable efficacy and safety in controlling myopia progression, providing effective treatment options for children and adolescents with mild to moderate myopia. However, differences in curvature changes and age-related effects warrant further attention.Keywords: orthokeratology, myopia control, children and adolescents, axial length, corneal curvature